Healthcare providers' hospital breastfeeding practices during the COVID-19 endemic and associated factors in Thailand: a cross-sectional study - Nongyao Lawin; Sasitara Nuampa; Chananchida Somsuk; Sutthisak Srisawad; Kasem Raungrongmorakot; Sukwadee Ketsuwan (BMC, 2024)
Abstract Background During COVID-19, healthcare providers were limited in their ability to provide breastfeeding support while women encountered breastfeeding difficulties. Enhancing appropriate breastfeeding care practices among healthcare providers in hospitals may improve the safety of breastfeeding during an endemic. However, little is known about the breastfeeding care practices by healthcare providers and associated factors during the endemic impact. Objective To investigate the effect of the endemic on breastfeeding care practices by healthcare providers in hospitals and examine their associated factors in Thailand. Methods A descriptive comparative design was conducted through an online survey with 350 healthcare providers across five regions of Thailand between January and March 2022. The convenience sampling was used to recruit healthcare providers who had at least two years of experience supporting breastfeeding practices and were full-time working in the obstetric and pediatric departments of public tertiary hospitals. Analysis of variance and the independent t-test with relevant statistical corrections were utilized for comparisons of associated factors on breastfeeding care practices in healthcare providers. Results The mean breastfeeding care practices in hospitals during the COVID-19 endemic by healthcare providers was 39.17 (SD = 4.64, range 23 to 50). Four factors were statistically significant differences in breastfeeding care practices score, including work position (F = 7.03, df = 2.0, p = 0.001), types of COVID-19 vaccination (F = 6.95, df = 2, p = 0.001), education (F = 4.78, df = 2, p = 0.009), and monthly family income (F = 4.25, df = 3, p = 0.006), respectively. In addition, dose of COVID-19 vaccination and types of COVID-19 vaccination were significantly associated with individual breastfeeding support in hospitals (p < 0.05). Conclusions Healthcare providers' breastfeeding care practices in hospitals during the COVID-19 endemic were mostly at a moderate level in the Thai context. Hospital policy for maternal and child health support should strongly recommend the effective and safe practice of breastfeeding to encourage mothers to continue their breastfeeding duration.